Agricultural sector, rural environment and biodiversity in the Central and Eastern European EU member states - Liira, Jaan; Aavik, Tsipe; Parrest, Oliver; Zobel, Martin (Acta Geographica Debrecina Landscape & Environment series, 2008)
During the second half of the 20th century, agriculture and the rural environment diverged in Western and Central and Eastern European countries (CEEC). CEE countries itself are heterogeneous in the respect of land use intensity and history. In the current review we focus on the comparison of the agricultural sector and threats on biodiversities of EU new-member countries from Central and Eastern Europe and the old EU(15) member states. The clustering of countries revealed groups distinguished according to the level of their economic productivity, discriminating mostly among eastern and western European countries. CEE countries sub-divided according to geographic region, including also some old members of the EU. Within the western cluster, two large sub-clusters became evident according to economy affected by altitudinal and climatic differences. Partly because there are still areas where the intensity of land use remained low, the biological diversity in many regions of Central and Eastern Europe has remained high. However, loss of extensively used habitats, the restoration on intensive agriculture, reforestation with exotic species and urbanization are major threats to nature in CEE countries. The estimated variability among CEE countries is caused by different historical and cultural backgrounds of those countries. Due to the complexity and geographical diversity of driving forces, there remains much uncertainty in the possible impacts of particular factors on land use. This complexity and diversity have to be considered when planning economic as well as ecological means for developing the agricultural sector and conserving biodiversity in the future of CEE countries.